BRDT gene sequence in human testicular pathologies and the implication of its single nucleotide polymorphism (rs3088232) on fertility. (28th May 2014) - Barda, S.; Yogev, L.; Paz, G.; Yavetz, H.; Lehavi, O.; Hauser, R.; Doniger, T.; Breitbart, H.; Kleiman, S. E.
Summary Bromodomain testis‐specific (BRDT) protein is essential for the normal process of spermatogenesis. Mutant mice that expressed truncated BRDT had impaired testicular histology with severely reduced sperm concentration and abnormal sperm morphology, while a model of knockout Brdt mice with no BRDT protein had complete meiotic arrest. A BRDT single nucleotide polymorphism (SNP) (rs3088232) was reported as being associated with infertility in men. We assessed testicular specimens of 276 azoospermic men who underwent testicular sperm extraction to search for specimens that showed spermatogenic impairments similar to those of mutant BRDT mice. Ten similar specimens were selected for BRDT gene sequencing and they revealed three NCBI‐reported SNPs (rs10783071, rs3088232 and rs10747493) variously distributed among them. Bioinformatics analysis predicted that they would not affect protein activity. Further assessment of rs3088232 frequency in a large group of non‐obstructive azoospermia men and fertile controls demonstrated no significant difference between them (27.2 and 21.7% respectively; p = 0.122, Fisher's exact test). We conclude that the testicular impairments observed in the 10 specimens were not a consequence of BRDT gene mutation. The association between BRDT rs3088232 and infertility that had been reported in other studies was not supported.